Kualitas dan Relevansi Kontekstualitas Hadis “Yassiruu Walaa Tu’assiruu” Perspektif Double Movement Fazlur Rahman - Khasani, Khiban; Huda, Muhammad Habib Zainul; Aminullah, Aminullah; Wulandari, Fitri (Fahima, 2025)
The misinterpretation of the original meaning of the hadith prompted the author to conduct this research. In fact, understanding hadith cannot be arbitrary, but must be in accordance with the rules of Ulumul Hadith. The hadith that the author wants to examine is the hadith of Taysir (Yassiruu Walaa Tu'assiruu) or the hadith related to “making things easier”. This research is qualitative research with library research data collection. Data processing is done by descriptive analysis, assisted by Fazlur Rahman's Double Movement Theory. The purpose of this study is none other than to determine the quality of the sanad matan, the contextuality of asbabul wurud, and also the relevance of the hadith Taysir (Yassiruu Walaa Tu'assiruu) from the perspective of Fazlur Rahman's Double Movement. The conclusions of this research are: (1) the quality of hadith “Yassiruu Walaa Tu'assiruu” is sahih both in terms of sanad and matan; (2) the contextuality of the hadith “Yassiruu Walaa Tu'assiruu” is related to: giving relief in the affairs of the hereafter, facilitating the affairs of others, and choosing the easy over the difficult; (3) the relevance of hadith Taysir (Yassiruu Walaa Tu'assiruu) Fazlur Rahman's Double Movement perspective is: always praying for ease, always preaching wisely, and always offering ease in Islam.